Development and productivity of pepper with the use of coverage in the ground (Revista de Ciências Agroveterinárias, 2023)
Worldwide, the production of vegetables, including peppers, is related to intensive soil management and, consequently, to soil degradation. The implementation of conservationist managements has been intensified to reduce the damage resulting from the production of conventional management. In this sense, the objective of the study was to evaluate the development and productivity of sweet pepper grown in a no-tillage system under different vegetation cover, indicating the species with the greatest potential for this use. Therefore, the treatments used were: Control (conventional management); millet; sunn hemp; combination of cover crops (millet and sunn hemp) and spontaneous plants. The variables evaluated were: net photosynthesis, stomatal conductance, CO2 concentration, transpiration, water use efficiency, instantaneous carboxylation efficiency and productivity. It was found that all coverages improved the characteristics of length and fruit mass. In terms of number of fruits per plant and productivity, the mix coverage surpassed the rest. Coverage with weeds resulted in higher intracellular concentration, stomatal conductance and transpiration, while the mix treatment made it possible to obtain higher net photosynthesis value, water use efficiency and instantaneous carboxylation efficiency. The greatest increase in production and photosynthetic capacity occurred in the use of millet and sunn hemp.
Keywords: Sustainability, soil protection, vegetation cover